2021
DOI: 10.2478/bjmg-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of the GHRL gene variant in the molecular pathogenesis of obesity

Abstract: Obesity is as a global health problem due to its interaction with complex chronic disorders such as cardiovascular disorders, type 2 diabetes mellitus (T2DM) and cancer. Despite the fact that pathogenesis of obesity is not yet clearly understood, it is associated with a combination of psychological, environmental and various genetic factors. Here, employing a case-control design, we aimed to examine the effects of the GHRL c.152C>T (p.Arg51Gln) (rs34911341) and c.214G>T (p.Leu72Met) (rs696217) markers on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…At present, it is generally recognized that genetic and environmental factors are the main causes of obesity 3 , 16 . Recent studies have shown that the intestinal microbiota, an environmental factor, is closely related to the occurrence and development of obesity 4 , 5 , 15 , 16 . Ilseung et al 18 generated a model of adiposity by administering subtherapeutic antibiotic therapy to young mice and evaluated changes in the composition and capabilities of the gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…At present, it is generally recognized that genetic and environmental factors are the main causes of obesity 3 , 16 . Recent studies have shown that the intestinal microbiota, an environmental factor, is closely related to the occurrence and development of obesity 4 , 5 , 15 , 16 . Ilseung et al 18 generated a model of adiposity by administering subtherapeutic antibiotic therapy to young mice and evaluated changes in the composition and capabilities of the gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…This amino acid residue is outside of mature ghrelin. In a study of Becer and Ergoren (2021), it has been shown that the frequency of the minor allele rs696217 T (Met72) was significantly higher in obese individuals. At the same time, in the study of Yadegari et al (2022) individuals with the TT genotype at the locus had the lowest prevalence of obesity compared to other genotypes among individuals.…”
Section: Tablementioning
confidence: 99%
“…[ 31 ] A dual effect of GHRL gene variants (i.e., rs34911341‐c.152C > T and rs696217‐c.214G > T) was reported in obesity and cholesterol metabolism in obese and non‐obese Turkish‐Cypriot subjects employing a case‐control study. [ 32 ] The rs696217 variant (c.214G > T) was found to be significantly higher in obese patients and in those with lower serum high‐density lipoprotein cholesterol than with the wild‐type genotype; hence, this susceptibility variant may be considered as a risk allele and a crucial marker for both obesity and cholesterol metabolism in this population and could potentially be implicated in clinical diagnosis and care.…”
Section: Introductionmentioning
confidence: 99%